Colelitíase em pacientes bariátricos: correlação da perda de peso com a incidência de colelitíase em pacientes após a realização do bypass gastrintestinal - Ferrari, Mário Antônio (2014)
Objective: Obesity treatment with Roux-en-Y gastroplasty has been widely used for the last few decades. Patients who undergo this surgery can develop gallstones in the months following the procedure, just as occur in people who lose weight with conventional treatments. The purpose of this study is to determine the incidence of cholelithiasis in patients that have had this surgery and to analyze its possible correlation with the rapidity of weight loss. Methods: A retrospective cohort of morbidly obese patients submitted to Roux-en-Y gastroplasty was studied. The patients were evaluated at specific times: Time 1 was before obesity treatment surgery, and Time 2 was postoperatively, before 12 months time had passed. During Time 2, the speed of weight loss and the occurrence or not of cholelithiasis within this period was noted. Results: Records of 1,161 patients were analyzed, 312 (26.9%) of which had cholelithiasis or had already had cholecystectomy preoperatively. Among the 849 remaining patients, 447 (52.6%) maintained follow-up for 6 months postoperatively, and 128 (28.6%) developed cholelithiasis during this period and presented with an average weight loss of 66.3 ± 16.8%. Between 7 and 12 months, 238 individuals completed the planned follow-up, and of these, 27 (11.3%) developed cholelithiasis and had an average weight loss 22.9 ± 9.8%. Conclusion: The time needed to lose weight appears to maintain a direct correlation to the development of cholelithiasis in patients who have undergone surgical obesity treatment, mainly in the first six months of postoperative.